2019
DOI: 10.1038/s41396-019-0538-1
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal nitrification is constrained by copper complexation with organic matter in municipal wastewater treatment plants

Abstract: Consistent with the observation that ammonia-oxidizing bacteria (AOB) outnumber ammonia-oxidizing archaea (AOA) in many eutrophic ecosystems globally, AOB typically dominate activated sludge aeration basins from municipal wastewater treatment plants (WWTPs). In this study, we demonstrate that the growth of AOA strains inoculated into sterile-filtered wastewater was inhibited significantly, in contrast to uninhibited growth of a reference AOB strain. In order to identify possible mechanisms underlying AOA-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 63 publications
0
34
0
Order By: Relevance
“…This could be explained by the accumulation of organic compounds under drought, some of which were shown to inhibit Nitrosotalea activity and growth in pure cultures [ 92 ] compared with other AOA such as N. viennensis and N. gargensis [ 88 , 93 ]. Furthermore, inhibition by organic compounds has been shown to be stronger in AOA than in AOB, although it varies between AOA strains [ 94 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the accumulation of organic compounds under drought, some of which were shown to inhibit Nitrosotalea activity and growth in pure cultures [ 92 ] compared with other AOA such as N. viennensis and N. gargensis [ 88 , 93 ]. Furthermore, inhibition by organic compounds has been shown to be stronger in AOA than in AOB, although it varies between AOA strains [ 94 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terrestrial environments, its bioavailability is influenced primarily by organic matter content and pH [ 13 ]. Recently, Gwak et al [ 14 ] showed that mixtures of organic compounds like yeast extract depleted Cu in culture experiments with AOA and AOB. However, only AOA growth was inhibited by reduced Cu bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the presence of anaerobic and anoxic phases, DPRS exhibits greater nitrification capacity and phosphorus removal performance than activated sludge [ 6 ]. But heavy metals can cause dysfunctions of proteins and inhibit microbial activities such as nitrification [ 7 , 8 ] and eventually attenuate the treatment efficiency [ 5 , 9 ]. Thus, a better understanding of the heavy metal-resistance strategies adopted by DPRS microbiomes might ultimately improve their robustness for nutrient removal.…”
Section: Introductionmentioning
confidence: 99%